Redox-Sensitive Linear and Cross-Linked Cystamine-Based Polymers for Colon-Targeted Drug Delivery: Design, Synthesis, and Characterisation - Yoke Mooi Ng; Siti Nur Aishah Mat Yusuf; Hock Ing Chiu; Vuanghao Lim (MDPI AG, 2020)
Cystamine-based polymers may help to achieve controlled and targeted drug delivery to the colon due to their susceptibility to breakage of the disulfide linkage in the low redox potential environment of the colon. In this study, two linear cystamine-based polymers with similar repeating units (LP1 and LP2) and a cross-linked cystamine-based polymer (BP) were synthesised and their kinetics and the various physical conditions underlying cystamine-based polymerisation were evaluated. In brief, N1,N6-bis(2-(tritylthio)ethyl)adipamide (2) was synthesised from the reaction of triphenylmethanol and cysteamine. Next, the trityl group of 2 was removed with trifluoroacetic acid and triethylsilane before proceeding to oxidative polymerisation of the end product, N1,N6-bis(2-mercaptoethyl)adipamide (3) to LP1. The Schotten-Bauman reaction was applied to synthesise LP2 and BP from the reaction of cystamine with adipoyl chloride or trimesoyl chloride. Scanning electron microscopy, energy-dispersive X-ray spectroscopy, and mapping showed that oxygen, nitrogen, sulfur, and carbon were homogenously distributed in the polymers, with LP2 and BP having less porous morphologies compared to LP1. Results of zinc-acetic acid reduction showed that all polymers began to reduce after 15 min. Moreover, all synthesised polymers resisted stomach and small intestine conditions and only degraded in the presence of bacteria in the colon environment. Thus, these polymers have great potential for drug delivery applications. LP2 and BP, which were synthesised using the Schotten-Bauman reaction, were more promising than LP1 for colon-targeted drug delivery.